The Effectiveness of Using Maternal and Child Health (MCH) Handbook through the 40 Days CARE Method for Independently Prevention of Postpartum Complications - Wardani, Endah Kusuma; Rachman, Machria; Rofika, Lutvia Dwi (Universitas Islam Lamongan, 2023)
The puerperium is the period after delivery up to 40 days when the reproductive organs recover. Postpartum services according to standards are provided to mothers and newborns from 6 hours to 42 days after delivery at least three times through home visits for early detection, treatment, or referral of complications that may occur during the postpartum period, as well as provide an explanation about health in general. One of the efforts made by the government is to procure MCH Handbook equipped with important information for mothers and babies, including screening for early detection of complications. Cadres will assist mothers in maximizing the utilization of MCH handbooks in the obedience of postpartum mothers to carry out postpartum visits, independent screening media for complications of the postpartum period and sources of receiving informational educational counseling during the postpartum period. This study aimed to analyze the effectiveness of using MCH handbook through the 40 Days CARE method for independently preventing complications in postpartum mothers. The design used was the Pre-Experiment (One Shot Case Study) with a sample of 30 respondents using a purposive sampling technique. Data collection used a questionnaire. Data analysis used T Test (α = 0.05). The results showed p value of 0.000, which means that there was an effect of using MCH handbook through the 40 Days CARE method on independently preventing complications in postpartum mothers. Based on this result, it is known that postpartum assistance has an influence and is effective in increasing the mothers’ independence in detecting and preventing postpartum complications, so the consistency in postpartum assistance and outreach to health cadres regarding this activity are badly needed